Agile project managment in the Turkish construction industry - Çardak, Fatih. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2019., 2019)
In today’s business world, companies need to be more agile and seek to adapt to new conditions faster than before due to rapidly developing technologies, fast evolving business needs and increasing competition. Within the context of construction industry, the common problems of construction projects, which are low productivity, poor performance, insufficient quality, delays in project schedule, and cost overruns, are often associated with complexity of projects and uncertain project environment. As a response to the need for a new management methodology to overcome these problems, Agile Project Management, which is originally developed by software developers, and its adoption has recently become quite popular in construction industry. It is an project management approach based on delivering project requirements incrementally through short iterations by a small, self-organized, cross-functional team. In order to explore factors affecting Agile PM implementation in the Turkish construction industry, an integrated framework composed of 6 constructs and corresponding 42 indicators is established based on in-depth literature review and expert opinions. The data collected through questionnaire survey is analyzed statistically and findings are evaluated accordingly. As a result, It is found to be promising and have a great potential especially in detailed design and construction stages to meet the needs of construction industry for performance improvement. However, the clear benefits is yet to be demonstrated in construction industry. Effective leadership of top management and professionals’ awareness of Agile PM is very critical at the beginning of implementation process. Besides, its recommended to combine Agile PM techniques with other management methods like lean, BIM, traditional PM etc. It is also found that that Agile PM doesn’t have direct impact on reduction of time and cost but focuses to prevent delays and cost overruns and to increase perceived quality and client satisfaction through improvements in responsiveness to change, transparency and visibility of the project, communication and organization learning within the project team, and finally reduction of the risk.
Keywords: Construction industry -- Turkey.; Project management -- Turkey.